Comparison of single intra operative versus an intra operative and two post operative injections of the triamcinolone after wedge excision of keloids of helix - Bashir, Muhammad Mustehsan; Ahmad, Hazqeel; Yousaf, Nadeem; Khan, Farid Ahmad (Journal of the Pakistan Medical Association, 2015)
To compare single intra-operative versus an intra-operative and two post-operative injections of triamcinolone after wedge excision of keloids of helix. The randomised controlled trial was conducted at the King Edward Medical University, Lahore, from January, 2011, to March, 2014, and comprised female patients over 14 years of age presenting with post-piercing keloids of helix not treated previously by any means and amenable to wedge excision. The subjects were divided into Group A who were given a single intra-operative injection of triamcinolone, and Group B who had an intra-operative and two post-operative injections of triamcinolone. Extra-lesional wedge excision of keloids was done, followed by infiltration of flaps and wound base with 0.5-1cc of triamcinolone 40mg/cc. Group B patients were given additional injections of triamcinolone at 1st and 2nd monthly visits. Both groups were observed for the evidence of hypertrophy or complications. Development of hypertrophy within one year of completion of treatment was considered recurrence. The 70 patients in the study were divided into two equal groups of 35(50%) each. The mean age of Group A was 22.34±4.95 years and that of Group B was 22.88±4.22 years (p=0.624). The Mean size of the keloids was 2.54±0.516 cm(2) in Group A and 2.61±0.569 cm(2) in Group B (p=0.613). Recurrence rate in Group A was 3(8.5%) and 2(5.7%) in Group B (p= 0.64). The complication rate was 3(8.5%) in Group A and 8(22.8%) in Group B (p=0.10). Single injection of triamcinolone was as effective as three in reducing recurrence with less complication rate.